The Implementation of Human Resource Development Program in Supporting Tourism in Parigi District Pangandaran Regency - Fitrichia Zhafira Agustiandini; Rizky Ilhami (Institute of Computer Science (IOCS), 2022)
This study aims to determine implementation to increase the capacity of human resources in supporting tourism in Parigi District, Pangandaran Regency.The research method used is qualitative. Data collection techniques used are interviews, observation and documentation. The results of this study illustrate that in supporting tourism in Parigi District, Pangandaran Regency, there are still several obstacles. One of them is that the available human resources have limited capabilities, so that the expected goals have not been fully achieved. However, from the aspect of communication, disposition, and bureaucratic structure, it has been going well